Immediate Postpartum Insertion of Intrauterine Contraceptive Device after Vaginal Delivery: Its Safety, Efficacy and Expulsion (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: postpartum intrauterine contraceptive device (PPIUCD); contraception; expulsion